Monocytes and dendritic cells are the primary sources of interleukin 37 in human immune cells. Issue 4 (23rd November 2016) - Rudloff, Ina; Cho, Steven X; Lao, Jason C; Ngo, Devi; McKenzie, Matthew; Nold-Petry, Claudia A; Nold, Marcel F
Abstract : IL-37 is produced and secreted by antigen-presenting cells, including monocytes and DCs, where IL-37 may act as an alarmin. Abstract: The interleukin (IL)-1 family member IL-37 is one of few anti-inflammatory cytokines, and it is capable of countering a broad spectrum of proinflammatory assaults. Although it is known that leukocytes are a major source of IL-37, knowledge on IL-37 production and secretion in specific immune cell types remains limited. Thus, we investigated IL-37 mRNA expression as well as protein production and secretion in human PBMCs. In PBMCs stimulated with agonists of Toll-like receptors (TLRs) 1–6 and 9, IL1F7 (the IL-37-encoding gene) was induced up to 9-fold, peaked at 6–8 h and returned to steady-state at 72 h. LPS-induced IL1F7 expression comprised isoforms b and c but not a and e . Flow cytometry revealed that among IL-37 + PBMCs, monocytes predominated (81–91%), but T cells (6–8%) and myeloid dendritic cells (mDCs, 1–2%) also contributed to the IL-37 + leukocyte pool. Monocytes and mDCs, but not T cells, were capable of secreting IL-37. Whereas monocytes and mDCs secreted IL-37 upon LPS stimulation, only mDCs also released IL-37 at steady-state. Among monocyte subsets, IL-37 was LPS inducible and secreted only in classical and, although less pronounced, in intermediate monocytes; secretion was observed as early as 3 h after stimulation. Overall, our data suggest that constitutive IL-37 secretion by mDCs may serve to maintain an anti-inflammatory milieu at steady state, whereas IL-37 is stored in monocytes to be available for rapid release upon inflammatory encounters, thus acting as a novel anti-inflammatory alarmin. These insights may prove important to advancing towards clinical use the protective functions of one of the most powerful anti-inflammatory mediators so far discovered.